Rethinking the Hollywood Teen Movie Gender, Genre and Identity - Smith, Frances (Edinburgh University Press, 2022)
An analysis of the Hollywood Teen Movie from a variety of key theoretical perspectivesRethinking the Hollywood Teen Movie is the first academic monograph to consider the aesthetic and narrative potential of this highly popular, yet often overlooked, film genre. Reconsidering tropes such as the male juvenile delinquent figure, the makeover and the teen vampire, the book uses a series of detailed case studies of key films like Rebel Without a Cause, Grease, Heathers and Twilight to explore the genre's relation to key critical concepts of intersectionality, postfeminism and the posthuman, and provides an innovative overview of the Hollywood teen movie and its construction of teen identity.Case studies include:Rebel Without a Cause (Nicolas Ray, 1955)Grease (Randel Kleiser, 1978)Heathers (Mark Lehmann, 1989)Pretty in Pink (Howard Deutch, 1986)She's All That (Robert Iscove, 1999)Mean Girls (Mark Waters, 2004)American Graffiti (George Lucas, 1973)Dirty Dancing (Emile Ardolino, 1987)Easy A (Will Gluck, 2010)Spider-Man (Sam Raimi, 2001)Twilight (Catherine Hardwicke, 2008)Chronicle (Josh Trank, 2012)
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Apr 2022)
Keywords: Film, Media & Cultural Studies; PERFORMING ARTS / Film & Video / Direction & Production; Teen films -- United States -- History and criticism; Teenagers in motion pictures